Ecology of riparian forests in Japan : disturbance, life history and regeneration - Sakio, H. (Springer, 2017)
Riparian forests along streams and rivers are diverse in species, structure, and regeneration processes, and have important ecological functions in maintaining landscape and biodiversity. This book discusses riparian forests from subpolar to warm-temperate zones, covering headwater streams, braided rivers on alluvial fans, and low-gradient meandering rivers. It presents the dynamics and mechanisms that govern the coexistence of riparian tree species, tree demography, the response to water stress of trees, and the conservation of endangered species, and focuses on natural disturbances, life-history strategies, and the ecophysiology of trees. Because many riparian landscapes have been degraded and are disappearing at an alarming rate, the regeneration of the remaining riparian ecosystems is urgent. With contributions by more than 20 experts in diverse fields, this book offers useful information for the conservation, restoration, and rehabilitation of riparian ecosystems that remain in world streams and rivers.